Stratigraphy and depositional environments of basin-fill sediments in southern Kathmandu Valley, Central Nepal - Paudel, Mukunda Raj; Sakai, Harutaka (Bulletin of the Department of Geology, 2008)
Quatenary fluvio-lacustrine basin-fill sediments in the southern part of the Kathmandu Basin was studied in order to clearify the stratigraphy and reconstruct the sedimentary environment during the initial stage of the Paleo-Kathmandu Lake. Six stratigraphic units; Tarebhir, Lukundol, Itaiti, Kalimati, Sunakothi Formations and Terrace gravel deposits, have been described based on field observation of lithology and sediment distribution. The Tarebhir Formation is the basal unit which is overlained by alluvial fan of the Itaiti Formation in the southern part and by the marginal lacustrine deposit of the Lukundol Formation towards the northern part. Further 3 km toward the north from the basin margin at Jorkhu the the Lukundol Formation is overlain by the open lacustrine facies of the Kalimati Formation. At the same locality the latter is overlain by fluvio-lacustrine facies of the Sunakothi Formation. Moreover, the Terrace gravel deposits erosionally cover the Sunakothi Formation. The Kalimati Formation thickens northward, while the Sunakothi Formation thickens between the central and southern part of the basin. The study shows that the Sunakothi Formation is of fluvio-lacustrine (fluvial, deltaic and shallow lacustrine) origin and extends continuously from the southern margin (~1400m amsl) to the central part (~1300m amsl) of the basin. It also indicates that sediments of this formation were deposited at the time of lake level rise and fall. Thick gravel sequence in the southern margin represents the alluvial fan before the origin (before 1 Ma) of the Paleo-Kathmandu Lake, while thick gravel sequence situated above the Sunakothi Formation is the Terrace gravel deposits of the late Pleistocene age (14C method), deposited during and after the shrinkage of the Paleo-Kathmandu Lake from south to north.   doi: 10.3126/bdg.v11i0.1544 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 11, 2008, pp. 61-70